1998
DOI: 10.1152/advances.1998.275.6.s59
|View full text |Cite
|
Sign up to set email alerts
|

Experiment demonstrating skeletal muscle biomechanics.

Abstract: Many students have limited opportunities to develop scientific expertise. This is caused, in part, by the scarcity of scientific educational materials and the expense of supplies and equipment. To address these concerns, we developed an inexpensive laboratory experience that introduces students to the scientific process. Our objective was to create an interactive experiment that requires minimal equipment. To this end, we created an exercise that examines muscle biomechanics. The students conduct a hands-on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In this sense, models are frequently used to explain complex ideas, since they incite logical reasoning and creativity, enabling students to develop conceptual or qualitative representations of the subject matter, directing them towards meaningful learning [2, 3, 8, 12, 14, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, models are frequently used to explain complex ideas, since they incite logical reasoning and creativity, enabling students to develop conceptual or qualitative representations of the subject matter, directing them towards meaningful learning [2, 3, 8, 12, 14, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that innovation in medical education is not an easy task [ 1 ], a considerable body of knowledge about cognitive processes and methods of teaching and learning has accumulated in recent decades, helping teachers to determine the most efficient way to teach. Scientific evidence has shown that active student participation facilitates the assimilation and consolidation of new knowledge, and improves learning outcomes [ 2 5 ]. In addition, literature favors the concept that information should be provided simultaneously in multisensory modalities, since a considerable amount of data indicates that the most complete and successful strategy for teaching physiology to a diverse group of students consists in offering information in a manner that addresses multiple learning styles [ 6 – 11 ], satisfying visual, aural and kinesthetic learners [ 2 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this model, the spring was stretched in 5-ml increments (5,10,15,20,25, and 30 ml in random order) by pulling down the syringe plunger. The spring recoil pressure was generated by releasing the syringe plunger.…”
Section: Resultsmentioning
confidence: 99%
“…A model was chosen because models significantly enhance student understanding (4). Simple, inexpensive models encourage research-oriented learning and are often used to explain complex ideas because models promote logic, reasoning, and creativity (1,2,(5)(6)(7)(8)(11)(12)(13)(14). Physical models relate the unknown to the familiar and provide a new perspective on information gathering.…”
mentioning
confidence: 99%